Combined effects of occupational exposure to hazardous operations and lifestyle‐related factors on cancer incidence. Issue 12 (28th October 2020) - Fukai, Kota; Kojimahara, Noriko; Hoshi, Keika; Toyota, Akihiro; Tatemichi, Masayuki
Abstract: We aimed to examine whether the number of types of hazardous operations at work experienced through a lifetime is associated with cancer incidence, and additionally examined the combined effects with lifestyle‐related factors. Using a nationwide, multicenter, hospital inpatient dataset (2005‐2015), we conducted a matched case‐control study with 1 149 296 study subjects. We classified the participants into those with none, 1, or 2 or more types of hazardous operation experience, based on information of special medical examinations taken, mandatory in Japan for workers engaged in hazardous operations. Using those with no experience as the reference group, we estimated the odds ratios for cancer incidence (all sites, lung, stomach, colon and rectum, liver, pancreas, bile duct, and bladder) by conditional logistic regression with multiple imputations. We also examined the effects of the combination with hazardous operations and lifestyle‐related factors. We observed increased risks for cancer of all sites, and lung, pancreas, and bladder cancer associated with the experience of hazardous operations. Multivariable‐adjusted ORs (95% CIs) of cancer incidence of all sites were 1 (reference), 1.16 (1.12, 1.21), and 1.17 (1.08, 1.27) for none, 1, and 2 or more types of hazardous operation experience, respectively ( P for trend <.001). Potential combined associations of hazardous operations with smoking were observed for lung, pancreas, and bladder cancer, and with diabetes for pancreas cancer. Engaging in hazardous operations at work and in combination with lifestyle‐related factors may increase the risk of cancer. We highlight the potential for those engaged in hazardous work to avoid preventable cancers. Abstract : Compared with those with no experience of occupational hazardous operation, the incidence of total, lung, pancreas, and bladder cancer was clearly increased as the number of types of hazardous operation work experience increased. Potential combined associations of hazardous operations with smoking were also observed for lung, pancreas, and bladder cancer, and with diabetes for pancreas cancer.